Modeling water availability under climate change scenarios: a systemic approach in the metropolitan area in Morelos, México - González-Zurita, Jazmín; Oswald-Spring, Úrsula (Frontiers in Water, 2024)
The research investigates integrated water management with complex socio-environmental interactions in worsening climate change scenarios. The proposed methodology involves the integration of Atmosphere–Ocean General Circulation Models (AOGCM) with Water Evaluation and Planning models (WEAP) to ensure water availability in the future. Two Shared Socioeconomic Pathways (SSP) integrate environmental, socioeconomic, and political elements under climate change scenarios with greater rainfall variability, extreme droughts, and floods in the metropolitan area of Morelos, located in the Center of México. Water availability in this region, along with population growth, industrialization, service activities, and agriculture, depends on forest conservation in the Ravines System of Northwest Morelos (RSNM). Public policy lacks interdisciplinary socio-environmental development, which prioritizes unsustainable economic growth overexploiting aquifers and polluting rivers. Official data from national and state governments do not reflect water conditions, and aquifer statistics date back decades. The majority of the analyzed models predict a delay in the monsoon, higher temperatures, extreme climate events, depletion of groundwater, and severe water scarcity during the hot months, rendering them unable to meet the increasing demand. This research provides valuable insights into the complex socioeconomic dynamics of a region with future water scarcity, which could be useful for similar conditions in the Global South.